Evaluation of radiation shielding, secondary radiation, and radiation damage in boron carbide and chromium diboride reinforced polymer composites - Ogul, Hasan; Akman, Ferdi; Ozdogan, Hasan; Kacal, Mustafa Recep; Tursucu, Ahmet; Polat, Hasan; Erkoyuncu, Ilhami (Elsevier Science Sa, 2025)
The presented work studies the radiation shielding effectiveness of polymer-based composites reinforced with B4C and CrB2 for both gamma-ray and neutron protection. The incorporation of CrB2 was found to significantly enhance gamma-ray attenuation, with the BCCrB-50 formulation demonstrating the highest shielding efficiency. Neutron shielding performance was also improved, particularly at thermal and fast neutron energies, with the additives playing a key role in reducing neutron transmission. Total Ionizing Dose (TID) and Displacement Per Atom (DPA) analyses were performed to assess the composites' radiation resistance, revealing that the BCCrB composites effectively minimize radiation exposure. These results suggest that BCCrB composites are a promising, environmentally friendly alternative for radiation shielding in various applications, including nuclear energy systems.
Keywords: Radiation shielding; Secondary radiation; Radiation damage; Chromium diboride